Analisis Daerah Rawan Longsor Berbasis Sistem Imformasi Geografis (Studi Kasus : Kabupaten Lima Puluh Kota, Sumatera Barat) - Jeffi Annisa; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Lima Puluh Kota is one of the regency in West Sumatera Province that prone to landslide, particularly when the rainfall intensity is high. Therefore, the research is conducted to determine the location that prone to landslide in Lima Puluh Kota regency in order to prevent the risk that potentially leads to disaster. The model that was applied to determine the prone landslide location is Indeks Storie, which would be treated in Geographic Information System’s program. Before that overlay process has been done, which was overlaying some of parameter maps (map of slope, map of soil types, map of rainfall, and map of land use) and marked the score in eachcriteria from the parameter maps. Based on the level classification analysis of Arifin S, et al (2006) Lima Puluh Kota regency is on the very low, low, and medium level of prone to landslide. This condition is contradicting with the actual fact. Based on level classification analysis of Nugroho, J.A, et al (2009) there are areas in Lima Puluh Kota that have very low, low, medium, high, very high level of prone to landslide which close to the actual fact. From the analysis in this map, the prone to landslide level in Pangkalan Koto Baru is very high, Sarilamak and surrounding areas have medium and high prone to landslide level, Harau subdistrict has high prone to landslide level, Gunung Omeh subdistrict has medium prone to landslide level.Keywords: SIG, Prone to landslide